2017
DOI: 10.1039/c7cp06945f
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the electronic structure of iron-(iii)-oxo oligomers forming in aqueous solutions

Abstract: The nature of the small iron-oxo oligomers in iron-(iii) aqueous solutions has a determining effect on the chemical processes that govern the formation of nanoparticles in aqueous phase. Here we report on a liquid-jet photoelectron-spectroscopy experiment for the investigation of the electronic structure of the occurring iron-oxo oligomers in FeCl aqueous solutions. The only iron species in the as-prepared 0.75 M solution are Fe monomers. Addition of NaOH initiates Fe hydrolysis which is followed by the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 72 publications
(103 reference statements)
2
16
0
Order By: Relevance
“…Although the [FeCl 2 (H 2 O) 4 ] +1 complex is most abundant (next to free Cl – ) in the bulk for 1.0 m FeCl 3 and higher concentration solutions, we cannot expect that speciation at the surface will be at all similar to bulk speciation due to the asymmetric hydration environment of the interface. Considering the enrichment of Fe­(III) in the surface region, one might expect polynuclear Fe­(III) species at the surface; however, Winter and co-workers recently found that iron-oxo oligomers are formed only when there is excess OH – …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the [FeCl 2 (H 2 O) 4 ] +1 complex is most abundant (next to free Cl – ) in the bulk for 1.0 m FeCl 3 and higher concentration solutions, we cannot expect that speciation at the surface will be at all similar to bulk speciation due to the asymmetric hydration environment of the interface. Considering the enrichment of Fe­(III) in the surface region, one might expect polynuclear Fe­(III) species at the surface; however, Winter and co-workers recently found that iron-oxo oligomers are formed only when there is excess OH – …”
Section: Resultsmentioning
confidence: 99%
“…Considering the enrichment of Fe(III) in the surface region, one might expect polynuclear Fe(III) species at the surface; however, Winter and co-workers recently found that iron-oxo oligomers are formed only when there is excess OH − . 122 Depicted in Figure 6, we show possible scenarios for the low and high concentration aqueous surfaces. For the high concentration, a centrosymmetric Fe(III) complex and the SFG-active hydrating water molecules as proposed from SFG spectral analysis (spectral fit, Supporting Information, Table S2) are depicted.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…4 Furthermore, core-level binding energies (BEs) are sensitive to covalent bonding interactions [5][6][7] and solute charge states, 8,9 relative peak intensities reveal stoichiometry 10,11 as well as surface propensity (via the so-called depth-probing technique), 12,13 and resonant signal enhancements can be used, e.g., to increase detection sensitivity. 5,14,15 These applications rely on extracting photoelectron (PE) peak areas and/or kinetic energies by taking into account experimental factors such as ionization and electron collection geometries, detection efficiency, and/or ionization cross sections (CSs), although the latter are typically unknown in the aqueous phase.…”
Section: Introductionmentioning
confidence: 99%
“…As the pH increases, the aqua ligands around the Fe 2+ center will deprotonate to form hydroxido ligand coordination before eventually collapsing to insoluble Fe 2+ -hydroxido nanoparticles. ,, Fe 3+ complexes have more complicated aqueous solution chemistry as Fe 3+ -hydroxyl complexes are stable as monomers in solution but can also form dimers, trimers, and polymers . The presence of small inorganic ions in solutions, especially Cl – ions, has been shown to generate large networks of polymeric species in solution by the use of resonant X-ray absorption spectroscopy on a liquid jet solution . Small inorganic ions are also known to have a propensity for the air–water interface and significantly affect the chemistry near the surface. …”
Section: Introductionmentioning
confidence: 99%